2007
DOI: 10.1080/00016340600984670
|View full text |Cite
|
Sign up to set email alerts
|

A survey of knowledge, attitude and practice of malaria management among pregnant women from two health care facilities in Nigeria

Abstract: This study has revealed that malaria is perceived as a common health problem among pregnant women attending these 2 health care facilities, and that knowledge, attitude and practice of its management is poor. Efforts should be made to improve anti-malarial intervention during pregnancy, to ensure that the goals of the Roll Back Malaria Initiative are achieved in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
23
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 4 publications
12
23
3
1
Order By: Relevance
“…This results is lower than the 89% recorded by Enato et al (2007) among pregnant women that attended two health facilities in Edo state, Nigeria but lower than the 11.8% recorded by Ruspashree et al (2014) in rural communities of Aliero local government area in Kebbi Sate, in northern Nigeria but higher than the 39.7% recorded in a study conducted in south-east Nigeria by Okeke and Okafor (2008).…”
Section: Prayer and Fasting In The Church Sacrifice And Visit To Shricontrasting
confidence: 52%
“…This results is lower than the 89% recorded by Enato et al (2007) among pregnant women that attended two health facilities in Edo state, Nigeria but lower than the 11.8% recorded by Ruspashree et al (2014) in rural communities of Aliero local government area in Kebbi Sate, in northern Nigeria but higher than the 39.7% recorded in a study conducted in south-east Nigeria by Okeke and Okafor (2008).…”
Section: Prayer and Fasting In The Church Sacrifice And Visit To Shricontrasting
confidence: 52%
“…The study found that over 60% of the participants did not receive health education on IPTp, resulting to low IPTp coverage [17]. Other studies such as [18] and [19] also confirm that knowledge about IPTp remains low among pregnant women in developing countries, which suggests that ANC facilities are not doing enough on sensitization. However, [15] links the knowledge gap to late and inconsistent ANC attendance.…”
Section: Factors Influencing the Uptake Of Intermittent Preventive Trsupporting
confidence: 50%
“…These findings are similar to those of other developing country studies, underscoring the way that traditional and modern beliefs and practices, both effective and ineffective, may coexist in developing societies. 12,15,[18][19][20] Similarly, our respondents exhibited faith in the capacity of clinicians and modern therapies to treat malaria, yet described the widespread use of traditional treatments ranging from mantra-reading to the ingestion of exotic concoctions. They also showed unawareness of ITNs and chemoprophylaxis, and highlighted issues of accessibility and affordability of major prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several studies conducted in malaria-endemic areas of Africa regarding attitudes and practices toward malaria control measures among pregnant women indicate that malaria is perceived as a serious illness, knowledge of malaria risks during pregnancy is relatively high, and contact with traditional healers and self-medication with local remedies is common. [15][16][17][18][19][20] In addition, pregnant women have limited confidence in the effectiveness of ITNs and intermittent preventive therapy for protection from malaria.…”
Section: Introductionmentioning
confidence: 99%